Studio Zhu Pei. Museo delle Fornaci Imperiali - Arrigoni, Fabrizio (Firenze Architettura, 2021)
At the Imperial Kiln Museum of Jingdezhen it is possible to recognise certain features that determine a general habitus which is active also at other latitudes. Among these: assessing the material and historical conditions of the individual contexts as premise for the project, the action on the public space of the city as element for the safeguarding and reactivation of the collective memory, and architecture understood as built-form, as meditation and practice on its immanent, concrete materiality.